2013
DOI: 10.1089/aid.2012.0313
|View full text |Cite
|
Sign up to set email alerts
|

Gardiquimod: A Toll-Like Receptor-7 Agonist That Inhibits HIV Type 1 Infection of Human Macrophages and Activated T Cells

Abstract: Immune response modifiers are being studied as therapeutic agents for viral infections and cancer. These molecules include agonists for the Toll-like receptors (TLR), a family of innate immune receptors. TLR7 and 8, located in cellular endosomes, bind single-stranded RNA characteristic of viral genomes, and trigger intracellular signaling pathways that induce inflammatory cytokines and antiviral innate immune factors. We studied the anti-HIV-1 effects of gardiquimod, a specific TLR7 agonist when used at concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Some novel methods and therapeutic strategies that can overcome viral latency have been developed such as HDAC, disulfiram, galectin-9, ingenol-3-angelate, prostratin, 5-azadC, bryostatin-1, and Runx1 [100, 101]. TLR7/8 agonists induce production of IFN-α that effectively inhibits HIV-1 replication in activated lymphocytes, macrophages or latently infected monocytic cell lines [102, 103]. Because HIV eradication is not achieved by highly active antiretroviral therapy, a strong rationale to investigate the curative potential of IFN-α is needed.…”
Section: Current Potential Applications Of Type I Ifn Classesmentioning
confidence: 99%
“…Some novel methods and therapeutic strategies that can overcome viral latency have been developed such as HDAC, disulfiram, galectin-9, ingenol-3-angelate, prostratin, 5-azadC, bryostatin-1, and Runx1 [100, 101]. TLR7/8 agonists induce production of IFN-α that effectively inhibits HIV-1 replication in activated lymphocytes, macrophages or latently infected monocytic cell lines [102, 103]. Because HIV eradication is not achieved by highly active antiretroviral therapy, a strong rationale to investigate the curative potential of IFN-α is needed.…”
Section: Current Potential Applications Of Type I Ifn Classesmentioning
confidence: 99%
“…These include the TLR7/8 agonist gardiquimod, which has been shown to induce the IFN-α that effectively inhibits HIV-1 replication in vitro in activated lymphocytes and macrophages at concentrations that activate TLR7 but not TLR8 (15). Activation of TLR7/8-mediated signaling pathways upon treatment with either single-stranded RNA or the small molecule TLR7/8 agonist resiquimod (R-848) greatly reduced the ability of lymphoid tissue to support HIV infection, with the stage of anti-HIV action likely to be after virus-host cell membrane fusion but before DNA integration into the host genome.…”
Section: Introductionmentioning
confidence: 99%
“…The TLR7/8 agonist R848 has been found to induce a block to HIV-1 replication in monocytes and MDMs [7, 8, 10]. To further investigate the mechanism by which the drug interferes with HIV-1 replication we used a VSV-G-pseudotyped reporter virus engineered to package the SIVmac accessory protein Vpx [36].…”
Section: Resultsmentioning
confidence: 99%
“…Buitendijk et al [7] demonstrated that TLR7 and TLR8 activation inhibit HIV-1 replication. Treatment of MDMs with the TLR7 agonist gardiquimod induced a block to infection of co-cultured, activated PBMC and treatment of activated PBMC with agonists specific for TLRs 3, 7, 8 and 9 blocked HIV-1 replication [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation